Spatial Changes In The Rantau Ulayat Area Case Study Tarok Nagari Kepala Hilalang - Oktavia, Asri Mariza; Suparwoko (Departement of Architecture, Universitas Islam Indonesia, 2022)
Population growth and expansion of urban and industrial areas in peri-urban areas and customary ulayat areas lead to spatial changes that have an impact on differences in the definition of the area, boundaries, location settings, and control of Mamak Pusako over collective inheritance land. One of the customary areas that have experienced this development is Tarok Nagari, the Head of Hilalang, Padang Pariaman Regency, West Sumatra, which is called the rantau which is the locus of this research. This spatial change research study needs to be carried out to examine the potential for spatial planning for the purposes of inheritance from generation to generation and the next generation. In this study, the method used is the normative approach of ulayat inheritance. The analysis was carried out qualitatively related to land use patterns with a normative approach (customary law). While quantitative is used for mapping the pattern of inheritance of customary land with the Behavior Mapping technique. Strengthening data from informants regarding the description of regional development is carried out with the support of Design Guidance Structure theory, land use triangle theory, regulations and related literature. Temporal data based on the period before and after the land inheritance process were obtained through interviews with indigenous peoples' leaders and resource persons as well as literature studies on related customary lands. The results of the research on inheritance land spatial planning based on the customary law approach (ulayat) provide ambiguity in setting and spatial arrangement. Meanwhile, the theoretical approach to Space Syntax is the existence of a network from the development of functions, and the potential for access. Where this process cannot be seen by the Mamak Pusako, it raises the issue of lack of spatial control that is far away and developing at this time. Key Words: ulayat land, customary law, spatial planning, behavior mapping.